(untitled) (Journal of Dhaka National Medical College & Hospital, 2017)
Appendectomy & Cholecystectomy are common abdominal operation worldwide. Before surgery, antibiotics are usually used in hospitals to avoid post-operative complications. 150 patients (age range 20-45 years) were taken from Dhaka National Medical College Hospital for interventional study. When patients were selected for appendectomy or cholecystectomy, either ciprofloxacin plus metronidazole or ceftriaxone plus metronidazole were given intravenously. The patients were divided into 2 groups. Group I received drugs ciprofloxacin plus metronidazole and group II received drugs ceftriaxone plus metronidazole. There were 48 & 27 cases of appendicitis in group I & group II respectively and 27 & 48 cases of cholecystitis in group I & group II respectively out of total 150 study subjects. It was observed that the rate of infection was 8% in group I and 10.6% in group II. J. Dhaka National Med. Coll. Hos. 2017; 23 (01): 26-28